IDNLearn.com offers a unique blend of expert answers and community insights. Discover the information you need quickly and easily with our reliable and thorough Q&A platform.
Sagot :
Sure, let's solve the problem of simplifying the expression [tex]\( 4 \sqrt[3]{192 x^3} + \sqrt[3]{81 x^3} \)[/tex].
1. Break down each term separately:
- For the first term, [tex]\( 4 \sqrt[3]{192 x^3} \)[/tex]:
- Observe that [tex]\( 192 = 2^6 \times 3 \)[/tex], hence we can rewrite [tex]\( 192 x^3 \)[/tex] as [tex]\( 2^6 \times 3 \times x^3 \)[/tex].
- Therefore, [tex]\( \sqrt[3]{192 x^3} \)[/tex] becomes [tex]\( \sqrt[3]{2^6 \times 3 \times x^3} \)[/tex].
Since [tex]\( \sqrt[3]{a \times b} = \sqrt[3]{a} \times \sqrt[3]{b} \)[/tex]:
- [tex]\( \sqrt[3]{2^6 \times 3 \times x^3} = \sqrt[3]{2^6} \times \sqrt[3]{3} \times \sqrt[3]{x^3} \)[/tex].
- [tex]\( \sqrt[3]{2^6} = 2^{6/3} = 2^2 = 4 \)[/tex].
- [tex]\( \sqrt[3]{x^3} = x \)[/tex].
Thus,
[tex]\[ \sqrt[3]{192 x^3} = 4 \times \sqrt[3]{3} \times x. \][/tex]
Incorporating the factor of 4 in front, the term becomes:
[tex]\[ 4 \sqrt[3]{192 x^3} = 4 \times 4 \sqrt[3]{3} \times x = 16 \sqrt[3]{3} x. \][/tex]
- For the second term, [tex]\( \sqrt[3]{81 x^3} \)[/tex]:
- Observe that [tex]\( 81 = 3^4 \)[/tex], hence we can rewrite [tex]\( 81 x^3 \)[/tex] as [tex]\( 3^4 \times x^3 \)[/tex].
- Therefore, [tex]\( \sqrt[3]{81 x^3} \)[/tex] becomes [tex]\( \sqrt[3]{3^4 \times x^3} \)[/tex].
- [tex]\( \sqrt[3]{3^4} = 3^{4/3} = 3 \times \sqrt[3]{3} \)[/tex].
- [tex]\( \sqrt[3]{x^3} = x \)[/tex].
Thus,
[tex]\[ \sqrt[3]{81 x^3} = 3 \sqrt[3]{3} x. \][/tex]
2. Combine the simplified terms:
- The expression now is:
[tex]\[ 4 \sqrt[3]{192 x^3} + \sqrt[3]{81 x^3} = 16 \sqrt[3]{3} x + 3 \sqrt[3]{3} x \][/tex]
- Combine like terms:
[tex]\[ = (16 + 3) \sqrt[3]{3} x \][/tex]
[tex]\[ = 19 \sqrt[3]{3} x \][/tex]
Therefore, the simplified form of the given expression is:
[tex]\[ \boxed{19 \sqrt[3]{3} x} \][/tex]
1. Break down each term separately:
- For the first term, [tex]\( 4 \sqrt[3]{192 x^3} \)[/tex]:
- Observe that [tex]\( 192 = 2^6 \times 3 \)[/tex], hence we can rewrite [tex]\( 192 x^3 \)[/tex] as [tex]\( 2^6 \times 3 \times x^3 \)[/tex].
- Therefore, [tex]\( \sqrt[3]{192 x^3} \)[/tex] becomes [tex]\( \sqrt[3]{2^6 \times 3 \times x^3} \)[/tex].
Since [tex]\( \sqrt[3]{a \times b} = \sqrt[3]{a} \times \sqrt[3]{b} \)[/tex]:
- [tex]\( \sqrt[3]{2^6 \times 3 \times x^3} = \sqrt[3]{2^6} \times \sqrt[3]{3} \times \sqrt[3]{x^3} \)[/tex].
- [tex]\( \sqrt[3]{2^6} = 2^{6/3} = 2^2 = 4 \)[/tex].
- [tex]\( \sqrt[3]{x^3} = x \)[/tex].
Thus,
[tex]\[ \sqrt[3]{192 x^3} = 4 \times \sqrt[3]{3} \times x. \][/tex]
Incorporating the factor of 4 in front, the term becomes:
[tex]\[ 4 \sqrt[3]{192 x^3} = 4 \times 4 \sqrt[3]{3} \times x = 16 \sqrt[3]{3} x. \][/tex]
- For the second term, [tex]\( \sqrt[3]{81 x^3} \)[/tex]:
- Observe that [tex]\( 81 = 3^4 \)[/tex], hence we can rewrite [tex]\( 81 x^3 \)[/tex] as [tex]\( 3^4 \times x^3 \)[/tex].
- Therefore, [tex]\( \sqrt[3]{81 x^3} \)[/tex] becomes [tex]\( \sqrt[3]{3^4 \times x^3} \)[/tex].
- [tex]\( \sqrt[3]{3^4} = 3^{4/3} = 3 \times \sqrt[3]{3} \)[/tex].
- [tex]\( \sqrt[3]{x^3} = x \)[/tex].
Thus,
[tex]\[ \sqrt[3]{81 x^3} = 3 \sqrt[3]{3} x. \][/tex]
2. Combine the simplified terms:
- The expression now is:
[tex]\[ 4 \sqrt[3]{192 x^3} + \sqrt[3]{81 x^3} = 16 \sqrt[3]{3} x + 3 \sqrt[3]{3} x \][/tex]
- Combine like terms:
[tex]\[ = (16 + 3) \sqrt[3]{3} x \][/tex]
[tex]\[ = 19 \sqrt[3]{3} x \][/tex]
Therefore, the simplified form of the given expression is:
[tex]\[ \boxed{19 \sqrt[3]{3} x} \][/tex]
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. Thank you for choosing IDNLearn.com for your queries. We’re committed to providing accurate answers, so visit us again soon.